Spinal cord‐predominant neuropathology in an adult‐onset case of POLR3A‐related spastic ataxia - Sytsma, Trevor M.; Chen, Dong‐Hui; Rolf, Bradley; Dorschner, Michael; Jayadev, Suman; Keene, C. Dirk; Zhang, Jing; Bird, Thomas D.; Latimer, Caitlin S. (Neuropathology, 2022)
Biallelic mutations in POLR3A have been associated with childhood‐onset hypomyelinating leukodystrophies and adolescent‐to‐adult‐onset spastic ataxia, the latter of which has been linked to the intronic variant c.1909 + 22G>A. We report a case of adult‐onset spastic ataxia in a 75‐year‐old man, being a compound heterozygous carrier of this variant, whose brain and spinal cord were for the first time investigated by neuropathological examination. We describe prominent degeneration of the posterior columns, spinocerebellar tracts, and anterior corticospinal tracts of the spinal cord in a pattern resembling Friedreich's ataxia, with a notable lack of significant white matter pathology throughout the brain, in marked contrast with childhood‐onset cases. Immunohistochemical examination for the POLR3A protein demonstrated no apparent differences in localization or staining intensity between the proband and an age‐matched control subject. We demonstrate the clinicopathologic description of POLR3A‐related neurodegenerative disease and also mention the differential diagnosis of the childhood‐onset hypomyelinating leukodystrophy and late‐onset spastic ataxia phenotypes.